How Far Does Screening Women for Domestic (Partner) Violence in Different Health-Care Settings Meet Criteria for a Screening Programme? Systematic Reviews of Nine UK National Screening Committee Criteria - Feder, G.; Ramsay, J.; Dunne, D.; Rose, M.; Arsene, C.; Norman, Richard; Kuntze, S.; Spencer, A.; Bacchus, L.; Hague, G.; Warburton, A.; Taket, A. (National Coordinating Centre for Health Technology Assessment, 2009)
Objectives: The two objectives were: (1) to identify, appraise and synthesise research that is relevant toselected UK National Screening Committee (NSC) criteria for a screening programme in relation to partner violence; and (2) to judge whether current evidence fulfils selected NSC criteria for the implementation of screening for partner violence in health-care settings.Data sources: Fourteen electronic databases from their respective start dates to 31 December 2006.Review methods: The review examined seven questions linked to key NSC criteria: QI: What is theprevalence of partner violence against women and what are its health consequences? QII: Are screeningtools valid and reliable? QIII: Is screening for partner violence acceptable to women? QIV: Are interventions effective once partner violence is disclosed in a healthcare setting? QV: Can mortality or morbidity be reduced following screening? QVI: Is a partner violence screening programme acceptable to health professionals and the public? QVII: Is screening for partner violence cost effective? Data were selected using different inclusion/exclusion criteria for the seven review questions. The quality of the primary studies was assessed using published appraisal tools. We grouped the findings of the surveys, diagnostic accuracy and intervention studies, and qualitatively analysed differences between outcomesin relation to study quality, setting, populations and, where applicable, the nature of the intervention. Wesystematically considered each of the selected NSC criteria against the review evidence.Results: The lifetime prevalence of partner violence against women in the general UK population rangedfrom 13% to 31%, and in clinical populations it was 13–35%. The 1-year prevalence ranged from 4.2%to 6% in the general population. This showed that partner violence against women is a major public health problem and potentially appropriate for screening and intervention. The HITS (Hurts, Insults, Threatens and Screams) scale was the best of several short screening tools for use in health-care settings. Most women patients considered screening acceptable (range 35–99%), although they identified potential harms. The evidence for effectiveness of advocacy is growing, and psychological interventions may be effective, but not necessarily for women identified through screening. No trials of screening programmes measured morbidity and mortality. The acceptability of partner violence screening among health-care professionals ranged from 15% to 95%, and the NSC criterion was not met. There were no cost-effectiveness studies, but a Markov model of a pilot intervention to increase identification of survivors of partner violence in general practice found that such an intervention was potentially cost-effective.Conclusions: Currently there is insufficient evidence to implement a screening programme for partner violence against women either in health services generally or in specific clinical settings. Recommendations for further research include: trials of system-level interventions and of psychological and advocacy interventions; trials to test theoretically explicit interventions to help understand what works for whom, when and in what contexts; qualitative studies exploring what women want from interventions; cohort studies measuring risk factors, resilience factors and the lifetime trajectory of partner violence; and longitudinal studies measuring the long term prognosis for survivors of partner violence.